Study of bus voltage instability in DC power network supply by PV solar [electronic resource] - Muhammad Hafiz Mohd. Rashdi, 1986- (2009)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2009